A cross sectional evaluation of a total smoking ban at a large Australian university - Burns, S.; Hart, E.; Jancey, J.; Hallett, J.; Crawford, Gemma; Portsmouth, L. (BioMed Central, 2016)
Background: Total smoking bans have been found to contribute positively to the health of non-smokers by reducing exposure to second-hand smoke, and to enhance the likelihood of cessation among smokers. Methods: Two cross-sectional electronic surveys of staff and students at a large Australian university were conducted prior (n = 969) and 1 year post (n = 670) the implementation of a smoke free campus policy. Demographics, tobacco use, intention to quit, attitudes towards smoking and smoking restrictions and awareness of and attitudes towards the campus smoking policy were measured. Results: Exposure to second-hand smoke (SHS) reduced significantly (p < 0.001) one year after policy implementation. Smoking prevalence was similar at both time periods (T1 9.3 %; T2 8.4 %) and over half of smokers indicated they were planning to quit smoking in the future (T1 65.5 vs T2 62.3 %). There was a significant increase in positive responses to the statement the campus should be totally smoke free including all outdoor areas at T2 compared to T1 (T1 60.8 vs T2 71.4 %; p < 0.001), however respondents felt there should be places on campus for smokers to smoke (T1 53.6 vs T2 47 %; p < 0.05). Conclusions: This study found a significant positive difference in exposure SHS after implementation of the total ban. Although prevalence of smoking in this study was low, the proportion of respondents who were contemplating smoking cessation suggests support for smokers would be beneficial. Continued awareness raising, education and enforcement is likely to enhance the long term outcomes of the total ban.